The income protection role of an EMU wide unemployment insurance system: The case of atypical workers - H. Xavier Jara; Agathe Simon (University of Essex, Institute for Social and Economic Research (ISER), 2021)
This paper evaluates the potential of a common unemployment insurance system for the Economic and Monetary Union (EMU-UI) to improve income protection of atypical workers, namely those in part-time and temporary contracts. We use EUROMOD, the European tax-benefit microsimulation model, to simulate entitlements to national and EMU-UI and assess their effects on the household disposable income of atypical workers in the event of unemployment. Our results show that there are sizable gaps in the coverage of national UI schemes between countries, with atypical workers having particularly low coverage rates. The introduction of an EMU-UI would reduce coverage gaps and increase net replacement rates, especially for atypical workers, and would protect a large share of the workforce against the risk of poverty. Extending eligibility for the EMU-UI to the self-employed would further improve income protection, reducing their risk of falling into poverty in the event of unemployment.
Keywords: C81; H55; I38; 330